Penerapan Metode Forward Chaining pada Sistem Pakar Pendeteksi Awal Omicron - Devi Ayu Indah Sari; Nofriadi Nofriadi; Mardalius Mardalius (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Omicron is a type of virus that is again spreading in Asahan Regency, especially at the Sidodadi Health Center due to. Many people do not pay attention to the disorder and the causes and symptoms that occur in the virus. To overcome this, it is necessary to have the technology to detect the initial symptoms of this virus. The purpose of this study was to create an expert system to detect the initial symptoms of omicron using the forward chaining method. This stage of research consists of analysis, design, implementation, and testing. The data collection techniques used are observations and interviews. Meanwhile, this system uses six cases as a reference to detect omicron symptoms, namely confirmed, probable, severe category, moderate category, mild category, and asymptomatic. Before this system is used, system testing of all functions on components using a black box is carried out. Our findings resulted in an expert system of early symptom detection of omicron that can display the results of patient diagnoses such as symptoms, cases, and solutions. The test results show that all components such as buttons, text inputs, and outputs are working properly according to the procedure. So that this system can be used by the health Center to help detect the initial symptoms of omicron that occur in patients, and can provide the best solution for patients treated at this health center.